2009
DOI: 10.3928/01477447-20090728-44
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Delaminated Acetabular Articular Cartilage in Femoroacetabular Impingement

Abstract: Lesions to articular cartilage can be difficult to treat and directly impact surgical outcome in hip arthroscopy. This article describes a direct cartilage suture repair technique for a young, active individual with full-thickness acetabular cartilage delamination. Lesions of this type are commonly seen with femoroacetabular impingement. A 17-year-old boy presented with bilateral hip pain greater in the right than left. Arthroscopic intervention for the right hip included direct cartilage repair for the cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…The cause of chondral and osteochondral defects occurring in FAI is subject to some debate. While most agree acetabular chondral delamination occurs as a result of shear forces created by the cam deformity [11,23,29,40,46,50,56,62], the cause of defects occurring remotely to the cam or pincer deformity is subject to more speculation. Charbonnier et al [12] demonstrated impingement and secondary femoral head subluxation in dancers with morphologically normal hips, and two studies have demonstrated decreased hip flexion and abduction in patients with FAI [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of chondral and osteochondral defects occurring in FAI is subject to some debate. While most agree acetabular chondral delamination occurs as a result of shear forces created by the cam deformity [11,23,29,40,46,50,56,62], the cause of defects occurring remotely to the cam or pincer deformity is subject to more speculation. Charbonnier et al [12] demonstrated impingement and secondary femoral head subluxation in dancers with morphologically normal hips, and two studies have demonstrated decreased hip flexion and abduction in patients with FAI [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Our review found a case report that presented direct cartilage repair as a possible technique to treat large delaminated full-thickness acetabular cartilage repairs. Sekiya et al [42] described a case of a 17-year-old boy presented with bilateral hip pain because of bilateral CAMtype FAI and a 1-cm delaminated unstable cartilage flap in the anterior-superior acetabulum. Arthroscopic microfracture underneath the flap of anterior-superior acetabular cartilage and an absorbable monofilament suture repair of the cartilage was conducted.…”
Section: Direct Cartilage Suture Repairmentioning
confidence: 99%
“…Thus, Sekiya et al [19] described a case of a 17-year-old male high school wrestler with bilateral CAM lesions as well as a 1 cm delaminated unstable cartilage flap in the anterior-superior acetabulum. The authors arthroscopically performed a microfracture underneath the flap of anterior superior acetabular cartilage and, due to flap instability, completed a suture repair of the cartilage with an absorbable polydiaxanone monofilament.…”
Section: Osteochondral Allograft Transplantationmentioning
confidence: 99%